Determination of copper in rose tea samples using flame atomic absorption spectrometry after emulsification liquid-liquid microextraction - Kartoglu, Bedrihan; Bodur, Suleyman; Zeydanli, Damla; Gover, Tugce; Ozaydin, Ecem; Bakirdere, Emine Gulhan; Bakirdere, Sezgin (ELSEVIER SCI LTD, 2024)
Rose tea infusion has gained popularity worldwide due to its health benefits. However, it is known that tea plants can be contaminated with heavy metals including copper. Hence, an accurate and applicable analytical method namely emulsification liquid-liquid microextraction based deep eutectic solvent - flame atomic absorption spectrometry (ELLME-DES-FAAS) was proposed to determine copper at trace levels in rose tea samples. Under the optimum experimental conditions, analytical figures of merit for the developed method were examined, and dynamic range, limit of detection (LOD) and limit of quantification (LOQ) were found to be 5.07-246.61 mu g/kg (mass-based) with 0.9992 coefficient of determination, 2.50 mu g/kg and 8.32 mu g/kg, respectively. A matrix matching calibration strategy was employed to boost recovery results, and the acceptable recovery results were recorded between 95.9 % and 118.4 %. According to recovery results, the developed analytical method can be safely employed to determine the concentration of copper in rose tea samples accurately.
Keywords: Copper; Emulsification liquid-liquid microextraction; Flame atomic absorption spectrometry; Rose tea; Matrix matching calibration; DEEP EUTECTIC SOLVENTS; EXTRACTION METHOD; PRECONCENTRATION; WATER; LEAD; Chemistry; Food Science & Technology; Nutrition & Dietetics